2022
DOI: 10.1038/s41598-022-14246-2
|View full text |Cite
|
Sign up to set email alerts
|

Demographic characteristics shape patterns of dawn swarming during roost switching in tree-dwelling Daubenton’s bat

Abstract: Frequent roost switching in fission–fusion societies of tree-dwelling bats is closely associated with swarming behaviour entailing ritualised night-time displays around the roost tree and/or at the roost entrance to signal its actual location, particularly immediately prior to sunrise. However, effects of demographic characteristics of individuals in this social behaviour remain unanswered. Using passive integrated transponders (PIT) and automatic readers, we recorded swarming activity of members of a Daubento… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 53 publications
0
1
0
Order By: Relevance
“…We observed that N. lasiopterus often makes several roost approaches and landing attempts before entering the roost, a behaviour that has been observed in other bat species also [15,27,56], and that has been referred to as ‘dawn swarming’ [57,58,59]. However, the observed behaviour does not truly conform with ‘swarming’, because bats mostly arrived at and entered the roosts during the night and one after the other rather than flying in groups around roosts.…”
Section: Discussionmentioning
confidence: 82%
“…We observed that N. lasiopterus often makes several roost approaches and landing attempts before entering the roost, a behaviour that has been observed in other bat species also [15,27,56], and that has been referred to as ‘dawn swarming’ [57,58,59]. However, the observed behaviour does not truly conform with ‘swarming’, because bats mostly arrived at and entered the roosts during the night and one after the other rather than flying in groups around roosts.…”
Section: Discussionmentioning
confidence: 82%